2019
DOI: 10.1186/s12936-019-2941-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure–activity relationship to predict the anti-malarial activity in a set of new imidazolopiperazines based on artificial neural networks

Abstract: Background After years of efforts on the control of malaria, it remains as a most deadly infectious disease. A major problem for the available anti-malarial drugs is the occurrence of drug resistance in Plasmodium. Developing of new compounds or modification of existing anti-malarial drugs is an effective approach to face this challenge. Quantitative structure activity relationship (QSAR) modelling plays an important role in design and modification of anti-malarial compounds by estimation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…About the investigated N-11-azaartemisinis) also exhibit the endoperoxide linkage necessary for antimalarial activity. Figure 3 shows the MEP maps for the N-11-azaartemisinins of the training set obtained by the inclusion of substituents in the N atom of the lactam function (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As one can see in this figure, the MEP maps are similar to artemisinin and 11-azaartemisinin in the 1, 2, 4 trioxane ring region, with the electron density of some molecules more concentrated in this region, indicating greater biological activity.…”
Section: Molecular Electrostatic Potential Maps For Artemisinin 11-az...mentioning
confidence: 99%
“…About the investigated N-11-azaartemisinis) also exhibit the endoperoxide linkage necessary for antimalarial activity. Figure 3 shows the MEP maps for the N-11-azaartemisinins of the training set obtained by the inclusion of substituents in the N atom of the lactam function (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As one can see in this figure, the MEP maps are similar to artemisinin and 11-azaartemisinin in the 1, 2, 4 trioxane ring region, with the electron density of some molecules more concentrated in this region, indicating greater biological activity.…”
Section: Molecular Electrostatic Potential Maps For Artemisinin 11-az...mentioning
confidence: 99%
“…Interestingly, another study demonstrated a 2D-QSAR model of 3133 compounds using 929 descriptors in which the study showed abysmal 14.2% accuracy [ 96 ]. A similar study applied Artificial Neural Networks with Levenberg–Marquardt algorithm (non-linear approach) on the anti-malarial activity of a set of 33 imidazolopiperazine compounds against 3D7 and W2 strains [ 97 ]. Results showed the potential of the suggested model for the prediction of 3D7 activity and more acceptable than W2 strain with R 2 train = 0.947, R 2 val = 0.959, R 2 test = 0.920.…”
Section: Approachmentioning
confidence: 99%
“…- For ROCK datasets: 6 molecular descriptors (related 2D descriptors such as ring count) Prediction of the biological activity of various phenols and Rho kinase (ROCK) inhibitors. ( 57 ) ANN Linear partial least squares (linear statistical method) Supervised 36 4 molecular descriptors: - minimum bond dissociation enthalpy - electron transfer enthalpy - proton affinity - hydration energy Prediction of antioxidant activity of flavonoids ( 58 ) RF ANN Supervised 91 166 molecular descriptors including: - structure - topology - molecular connectivity index - geometric descriptors Prediction of the carcinogenicity of polycyclic aromatic hydrocarbons ( 59 ) ANN Supervised 33 6 molecular descriptors (related 2D and 3D descriptors) Prediction of anti-malarial activity of imidazolopiperazine compounds ( 60 ) ANN SVM Supervised 639 341 molecular descriptors related to: - simple constitutional - topological indices - electrotopological state indices - charge-based - hydrogen-bonding descriptors Prediction of nephrotoxicity of traditional Chinese medicines ingredients ( 61 ) * The top-ranked machine learning methods in each of these studies demonstrated better predictive ability than the other machine learning methods tested. ANN artificial neural network, SVM support vector machine, DT decision tree, RF random forest, KNN K-nearest neighbor, RBFNN radial basis function neural network …”
Section: Applications Of Machine Learning In Pharmaceutical Sciencesmentioning
confidence: 99%